2020
DOI: 10.1111/joa.13252
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitectural analysis of the neuron‐to‐glia association in the dorsal root ganglia of normal and diabetic mice

Abstract: Dorsal root ganglia (DRGs) host the somata of sensory neurons which convey information from the periphery to the central nervous system. These neurons have heterogeneous size and neurochemistry, and those of small-to-medium size, which play an important role in nociception, form two distinct subpopulations based on the presence (peptidergic) or absence (non-peptidergic) of transmitter neuropeptides. Few investigations have so far addressed the spatial relationship between neurochemically different subpopulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 36 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…In rats with diabetic neuropathy induced by streptozotocin (STZ) administration (Viisanen et al, 2020) BT44 treatment resulted in the decrease in the area (Figure 2D), but did not influence in the number of IBA1positive cells (Figure 2E). This result is fully in line with recently published data of Ciglieri et al (2020). These authors observed cytoarchitectonic changes related to glia-neuronal interactions in DRGs upon the treatment with STZ, while the overall number of SGC remained largely unaffected.…”
Section: Targeting Gfl Receptors With Small Molecules or Proteins Downregulate Glial Marker Expression In Surgery And Diabetes-induced Nesupporting
confidence: 92%
See 1 more Smart Citation
“…In rats with diabetic neuropathy induced by streptozotocin (STZ) administration (Viisanen et al, 2020) BT44 treatment resulted in the decrease in the area (Figure 2D), but did not influence in the number of IBA1positive cells (Figure 2E). This result is fully in line with recently published data of Ciglieri et al (2020). These authors observed cytoarchitectonic changes related to glia-neuronal interactions in DRGs upon the treatment with STZ, while the overall number of SGC remained largely unaffected.…”
Section: Targeting Gfl Receptors With Small Molecules or Proteins Downregulate Glial Marker Expression In Surgery And Diabetes-induced Nesupporting
confidence: 92%
“…These authors observed cytoarchitectonic changes related to glia-neuronal interactions in DRGs upon the treatment with STZ, while the overall number of SGC remained largely unaffected. In particular, STZ differentially affected the expression of SGC marker surrounding different subpopulations of DRG neurons and disturbed glia-neuron and neuron-neuron contacts in this tissue (Ciglieri et al, 2020).…”
Section: Targeting Gfl Receptors With Small Molecules or Proteins Downregulate Glial Marker Expression In Surgery And Diabetes-induced Nementioning
confidence: 92%
“…46 The glial layer could also be discontinuous leading to a direct contact between membranes of two adjacent neurons. 47,51 SGCs around DRG neurons are connected each other by gap junctions consisting of protein connexins 46 and the most abundant so far described in SGCs are Cx43 and Cx32. 52,53 Moreover, SGCs show dye coupling as observed after injection with Lucifer yellow.…”
Section: Satellite Glial Cellsmentioning
confidence: 99%
“…54 These features clearly indicate that SGCs carry out several important functions for DRG homeostasis, providing trophic and mechanical support for sensory neurons, regulating ion concentration, diffusion and trafficking of molecules between neurons. 48 SGCs can be identified by the expression of several glial markers such as glutamine synthetase, 51,55 GFAP, 44,56,57 S-100, 58,59 vimentin, 58 Cx42, 53 Kir4.1 potassium channels 60 transporters. 45,61 In particular, Nascimento and colleagues 58 have postulated the existence of a heterogeneous population of SGCs in DRGs after the observation that the expression pattern of S-100 and vimentin in SGCs is related to the neuron size they enwrapped.…”
Section: Satellite Glial Cellsmentioning
confidence: 99%
See 1 more Smart Citation